Desenvolvimento de página de vendas a partir do processo projetual mercadológico com base nas metodologias acadêmicas - Guedes, Stefany de Castro (Brasil, 2023)
The purpose of this project is to study the academic methodology of design with the methodology applied in the labor market, with emphasis on the conflicts between the two and on the specificities of the business reality. Through an analysis of classic design authors, such as Gui Bonsiepe and Bruno Munari, the study sought to establish a correlation between theories and business practice and this perception regarding the differences between one methodology over the other, was further corroborated by developing the project to create a sales page, which was the object of study in this research, in order to show that, in fact, academic design methods are not followed diligently in the job market. The specific objectives reached included the understanding of the importance of using methods in the development of works, in the verification of the time and activities of each stage of the academic and marketing methodologies, making an association between them, and a case study citing the methodological stages related to the methods oriented in the academy, to finally understand the dynamics and restrictions of the labor market, and the identification of differences between the two methodologies. The results obtained at the end of this study highlighted the need to adapt academic methodologies to the job market, the importance of effective communication and restrictions on creative freedom. The survey also pointed out difficulties in terms of the availability of detailed information and the complexity of the interactions involved in the project. Finally, the research concluded that traditional academic methods are not strictly followed in the professional environment due to their complexity and the need to adapt them to the constraints of the labor market. Therefore, it becomes imperative to correlate several methods or adopt a single one, depending on how the technique will help in the development and completion of the product.